Kebijakan Reformasi Maqâshid al-Syarîah dan Kontribusinya dalam Formulasi Alternatif Keringanan Pidana Penjara - Kamalludin, Iqbal; Arief, Barda Nawawi (al-'adalah, 2018)
Criminal law is often built on the paradigm of giving suffering to perpetrators of crime. This paradigm is no longer in accordance with the concept of modern punishment which focuses on efforts to foster criminals so that they would no longer repeat their actions. The changes in the paradigm of punishment, to some extent, have been accommodated by Article 73 of the Criminal Code Bill which contains alternative provisions/criminal sanctions.in jail. With this provision, a prisoner with one year or under punishment is able to repay his sentence as long as there are certain emergency conditions leading to a precarious situation/worry to him if he has to undergo consecutive penalties. This study tries to examine the new provision, using a normative juridical approach from the perspective of Islamic law. This study concludes that the paradigmatic change in punishment as shown in article 73 of the Criminal Code Bill has conformity with the perspective of maqâshid al-syarî’ah which put forward the 5 (five) main objectives in the law, namely maintaining and nurturing religion (al-dîn), soul (al-nafs), descent (al-nasl), wealth (al-mâl), and mind (al-aql).